(untitled) (Research, Society and Development, 2025)
Mental disorders represent a growing challenge for public health, requiring innovative approaches that consider factors beyond the traditional brain-mind axis. In this context, the gut microbiota has emerged as a key element, given its influence on the gut-brain axis and its relationship with mental health. This study aims to investigate the importance of gut microbiota modulation in mental health, focusing on the role of diet as a strategy for controlling mental disorders. This is a narrative review, seeking to synthesize relevant information on the relationship between gut microbiota and mental disorders. The methodology includes the search for scientific articles published between 2006 and 2024 in the PubMed, SciELO, and BIREME databases. After the initial screening, which included reading titles and abstracts, articles on microbiota interventions and their impacts on mental health were critically analyzed. According to the analyzed articles, the treatment of mental issues can be enhanced by strategies involving gut microbiota modulation, especially using probiotics, prebiotics, and symbiotics, as well as dietary interventions that prioritize fresh, fiber-rich foods. These approaches demonstrated positive effects in reducing symptoms such as anxiety, depression, and cognitive alterations, reinforcing the connection between diet, microbiota, and mental health. It is concluded that gut microbiota modulation represents a promising and complementary path in mental health care, with diet being a central tool in this process.